2008
DOI: 10.1186/1472-6963-8-35
|View full text |Cite
|
Sign up to set email alerts
|

Differences in pharmaceutical consumption and expenses between immigrant and Spanish-born populations in Lleida, (Spain): A 6-months prospective observational study

Abstract: Background: There are few studies comparing pharmaceutical costs and the use of medications between immigrants and the autochthonous population in Spain. The objective of this study is to evaluate whether there are differences in pharmaceutical consumption and expenses between immigrant and Spanish-born populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…Studies in Spain have highlighted differences in the health care services provided to immigrants and to the native-born population with regard to pharmaceutical consumption and the use of emergency hospital services (7,8). However, no studies to date have analyzed sick leave among immigrants living in Spain, and only a few have concerned sick leave among immigrants in Europe (9)(10)(11)(12).…”
Section: Soler-gonzález Et Almentioning
confidence: 99%
“…Studies in Spain have highlighted differences in the health care services provided to immigrants and to the native-born population with regard to pharmaceutical consumption and the use of emergency hospital services (7,8). However, no studies to date have analyzed sick leave among immigrants living in Spain, and only a few have concerned sick leave among immigrants in Europe (9)(10)(11)(12).…”
Section: Soler-gonzález Et Almentioning
confidence: 99%
“…Use of medicines constitutes an important part of many medical treatments and disease prevention interventions. Some studies on drug utilization in Spain have observed that immigrants consume fewer medicines and have much lower expenditures on pharmaceuticals compared to the autochthonous population 7,8 . Another aspect modulating drug utilization patterns of migrants is the possible lack of trust in the proposed treatment and as a consequence, poor compliance.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the previous Spanish literature on this topic [6,12], this study uses a large health-related national wide dataset that allows us to conduct a detailed comparison of drug consumption between Spaniards and several categories of immigrants, thus taking into account the heterogeneity inherent to the immigrant collective living in Spain. In addition, this paper uses a richer set of variables than previous studies about drug consumption in Spain, such as type of health insurance and AC, two important determinants of drug coverage in this country.…”
Section: Discussionmentioning
confidence: 98%
“…For the case of Spain, a recent report shows that the (age-sex adjusted) pharmaceutical spending of immigrants is much lower than that of their Spanish counterparts [11]. The findings of the study by Rue et al for the city of Lleida in Catalonia suggest that both pharmaceutical drug spending and drug consumption are lower for non-Spanish-born individuals relative to Spanish-born individuals with the same age and sex [12]. Finally, the only national level study based on the 2003 Spanish National Health Survey corroborates the previous results for Catalonia showing that, as compared to the Spanish population, non-Spanish nationals consume fewer medications [6].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation